REPARTIŢIA ELEMENTELOR DIN GRUPA TR ÎN STRATELE DE VÂRSTĂ VENDIANĂ DIN REGIUNEA CENTRALĂ A BAZINULUI r. NISTRU - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2008)
In the lithologic formations of the northern part of Republic Moldova considerably big concentrations of the TR Group elements have been discovered such as La, Ce, Yb, Y and Sc. These elements and their chemical components are applied in a variety of different fields: chemistry, optics, metallurgy, cosmonautics and aeronautics, electronics, atomic energy, etc. The geological premises for the TR Group elements presence in the Nistru River area are considerably high and, taking into consideration their exclusive importance for the modern technologies, some Geological and Geochemical prospecting’s can be projected aiming to solve the problem for localization of some TR significant accumulation within the terrigenous stratums.